Sustainable Structures and Construction in Civil Engineering - Chen, Zhihua; Yang, Qingshan; Wu, Yue; Du, Yansheng (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
With the development of society and the economy, sustainable structures and construction are becoming increasingly necessary in civil engineering. Sustainability in construction refers to eco-friendly and economical practices that occur throughout the whole life cycle of structures, including their design, construction, service and demolition. Sustainable structures include fabricated and modular structures, structures constructed using bio-based materials, as well as others. Specifically, timber, bamboo and light steel have become increasingly popular building materials. Additionally, wall panels made from eco-friendly materials can be used to reduce buildings' energy consumption and carbon emissions. Sustainable construction necessitates prefabricated construction and the recycling and reuse of materials, structures, etc. Key problems have been proposed and solved in regard to sustainable structures and construction in practice. This Special Issue provides an international forum for the presentation and discussion of the latest developments in sustainable structures and construction in civil engineering. The topics of interest include the modeling, testing and construction of sustainable structures. Original papers focused on all aspects of sustainable structures and construction have been accepted for publication.